Judicial Interpretation of Land Registration and Legal Protection in Indonesia Between Administrative Evidence and Substantive Justice - M. Filusi Ardiansyah; Faisal Santiago (Greenation Research & Yayasan Global Resarch National, 2025)
Land registration plays a central role in Indonesia’s land administration system and is widely regarded as a primary instrument for achieving legal certainty. In judicial practice, however, land registration does not function merely as an administrative record but also as a crucial element in evidentiary assessment during land dispute resolution. Courts are frequently required to interpret the legal status of registered land certificates in relation to substantive land rights that may arise from possession, inheritance, contractual relations, or customary law, placing judicial interpretation at the intersection between administrative certainty and substantive justice. This article examines how Indonesian courts interpret land registration within the broader framework of legal protection for land rights holders. Using a normative juridical research method, the study analyzes statutory regulations governing land registration, legal doctrines concerning declarative and constitutive registration systems, and selected judicial decisions in land dispute cases. The analysis focuses on the manner in which judges balance the evidentiary value of land certificates with proof of substantive land relations. The findings demonstrate that Indonesian courts do not consistently treat land registration as absolute or conclusive proof of rights. While land certificates are generally regarded as strong administrative evidence, judicial reasoning often allows for recognition of substantively valid rights that predate or exist independently of registration. This approach reflects an implicit acknowledgment of the declarative nature of land registration, even when administrative practice tends toward formalism. The article argues that judicial interpretation plays a decisive role in preserving the protective function of land law by preventing administrative formalism from overriding substantive justice. Strengthening this interpretative approach is essential to ensure that land registration supports legal certainty without marginalizing legitimate land rights within Indonesia’s pluralistic agrarian legal framework.